Degradation Analyses of Commercial Lithium-Ion Cells by Temperature/C-rate Controlled Cycle Test. (6th April 2015) - Matsuda, Tomoyuki; Myojin, Masao; Ando, K; Imamura, Daichi
Abstract : Cycle life tests of commercial 18650-type lithium-ion cells were conducted at temperatures of 0°C, 25°C, and 45°C and current rates of 1 C and 2 C. Surprisingly, the discharge capacity rapidly decreased at 0°C regardless of the current rate. On the other hand, the discharge capacity decreased faster at 45°C than at 25°C for a rate of 1 C, and this decrease was faster at 25°C than 45°C for a rate of 2 C. Electrodes and electrolytic solutions of the degraded cells were characterized by several analytical methods. X-ray photoelectron spectroscopy revealed differences between solid electrolyte interface components according to test temperature. The carbonate ratio was high at low temperature while the phosphate ratio was high at elevated temperature. The observed cell degradations were caused by several factors exhibiting various temperature and current rate dependencies.